1999
DOI: 10.1210/jcem.84.7.5839
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens Alter Adrenocortical Function: Genistein and Daidzein Suppress Glucocorticoid and Stimulate Androgen Production by Cultured Adrenal Cortical Cells1

Abstract: Phytoestrogens influence a variety of biological processes. As 17beta-estradiol alters adrenocortical cell function, we examined whether the dietary phytoestrogens, genistein and daidzein, have related effects. In cultured human fetal and postnatal adrenal cortical cells, genistein and daidzein (both 0.4-40 micromol/L) decreased ACTH-stimulated cortisol production to basal levels (ED50, 1-4 micromol/L). In the adult adrenocortical cell line, H295, genistein, daidzein, and 17beta-estradiol (10 micromol/L) decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In theory, isoflavones may influence estrogen action by virtue of effects on enzymes involved in steroid metabolism, such as aromatase (Rice, Mason, and Whitehead 2006), 17bhydroxysteroid dehydrogenases, steroid sulfatases and sulfotransferases (Lacey et al 2005), among others (Mesiano et al 1999;Ohno et al 2002). Isoflavones could also affect biologically active levels of hormones by affecting SHBG concentrations (Loukovaara et al 1995).…”
Section: Reproductive Hormonesmentioning
confidence: 99%
“…In theory, isoflavones may influence estrogen action by virtue of effects on enzymes involved in steroid metabolism, such as aromatase (Rice, Mason, and Whitehead 2006), 17bhydroxysteroid dehydrogenases, steroid sulfatases and sulfotransferases (Lacey et al 2005), among others (Mesiano et al 1999;Ohno et al 2002). Isoflavones could also affect biologically active levels of hormones by affecting SHBG concentrations (Loukovaara et al 1995).…”
Section: Reproductive Hormonesmentioning
confidence: 99%
“…However, the literature regarding the effects of isoflavones on HPA axis reactivity and behavior is less clear. Most studies in animals have found that isoflavonesare beneficial leading to anxiolytic effects on behavior and HPA axis reactivity, based on their increased affinity for ERβ (Mesiano et al, 1999;Lephart et al, 2002;Lephart et al, 2003). However, other studies have found varying results including anxiogenic or no effect on behavior (Hartley et al, 2003;Bu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies looking at the effects of isoflavones on HPA axis reactivity have shown increases and decreases, as well as no effect on CORT secretion (Mesiano et al, 1999;Hartley et al, 2003;Lephart et al, 2003;Lephart et al, 2004;Bu et al, 2005). Furthermore, the presence of isoflavones in an animal's diet have been shown to modulate behavioral outcome, producing both anxiolytic and anxiogenic type of effects on behavior (Lephart et al, 2002;Hartley et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol is a steroidal hormone that increases blood sugar levels through improving carbohydrate, fat, and protein metabolism as well as gluconeogenesis. In adrenocortical cell lines, genistein treatment suppressed the cAMP-stimulated cortisol synthesis (Mesiano et al, 1999). Moreover, genistein is involved in the modulation of cellular and humoral immunity at multiple levels, such as the inhibition of the activation of NFκB and the reduction of inflammatory cytokine levels (Jonas et al, 1995), which indicate that genistein has anti-inflammatory functions.…”
Section: Pharmacological Effectmentioning
confidence: 99%